PENGARUH APLIKASI VIRGIN COCONUT OIL TERHADAP PENINGKATAN JUMLAH FIBROBLAS PADA LUKA PASCA PENCABUTAN GIGI PADA RATTUS NOVERGICUS - Anggun Hibah Jannah Tamara; Yayun Siti Rochmah; Rochman Mujayanto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background: Wound healing is a complex biological process. Fibroblast is one of cell which is responsible for the wound healing process. Virgin Coconut Oil (VCO) have health benefit as antibacterial, antiinflamatory, antioxidant, and immunomodulatory. This research was purposed to know the influence use of VCO over the amount of fibroblast in wound healing after dental extraction.Method: Research quasi experimental with post test control group design and using 15 Rattus novergicus which were divided into three groups (control positive, VCO topical application, and VCO per oral application). Tooth removal was committed by using explorer, scalpel-blade, and arterial clamp. Then VCO applied everyday for 7 days. Day 7th Rattus novergicus were died, the socket after extraction were made into histological form, then the amount of fibroblast were counted with 5 field of views and made in average. Result: The number of fibroblast of the most numerous was VCO per oral ( 48,6 ± 49,8 ), VCO topical ( 36,2 ± 38,8 ), and control positive ( 33,4 ± 35,2 ). The results of the Saphiro Wilk test and Levene test acquired data normally distributed and homogeny, so it continued to One Way Anova and data showed there were significant difference among the groups of samples with value p<0,05.Conclusion: The conclusion of this research is VCO could increase the number of fibroblasts in wound healing after dental extractions